Perlindungan Hak Asasi Manusia Pada Era Pengawasan Digital Oleh Negara: Analisis Hukum Tentang Privasi Vs Keamanan - Ananda, M. Rizki; Ikraam, Akhmad (Riviera Publishing, 2026)
The development of information technology in the digital era has transformed the way states conduct surveillance on citizens. The use of digital technology allows states to efficiently collect, process, and analyze data, leading to the emergence of digital surveillance, such as communication wiretapping, artificial intelligence-based surveillance cameras, and monitoring of social media activity. Although claimed to maintain security and order, digital surveillance risks violating the rights to privacy and freedom of expression. This study analyzes human rights protection in digital surveillance by the state using a normative juridical approach, examining national regulations, international law, and academic literature. The results show that digital surveillance regulations in Indonesia are still limited and fragmented. Furthermore, weak oversight mechanisms open up room for abuse of authority that can violate citizens' constitutional rights. This study emphasizes the need for strengthened digital surveillance regulations that focus on human rights protection, increased policy transparency, clear limitations on authority, and the establishment of an independent oversight body to ensure digital surveillance complies with democratic principles and the rule of law.